Animal Welfare and Eggs – Cheap Talk or Money on the Counter? - Laura Mørch Andersen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2010)
We estimate revealed willingness to pay for animal welfare using a panel mixed logit model. We utilize a unique household level panel, combining real purchases with survey data on perceived public and private good attributes of different types of eggs. We estimate willingness to pay for organic eggs controlling for trust in a positive connection between the public good animal welfare and the organic label and the private good food safety also connected to the label. Our results suggest that in the real world, animal welfare plays a minor role in the demand for agricultural products.
Keywords: Q31; D12; 330; animal welfare; panel mixed logit; market purchase data; labelling; willingness to pay; altruism